A Penerapan Kriteria Taman Kota di Jakarta Timur: Studi Kasus: Taman PKP - Susilawati, Ela; Murti, Margaret arni Bayu; Putri, Ramadhani Isna (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
DKI Jakarta Province is the capital of Indonesia which had a population of 10,467,600 people. Population growth and an increase in the city's built-up area cause green open space for the ecological balance and create the city's aesthetics. PKP Park, located in Ciracas District, East Jakarta, has Situ Rawa Babon, which suited the aesthetic identity. Thus, this place attracts visitors. However, based on the observation results, the condition of the PKP Park still has some weaknesses, which raises the need for research to examine the application of city park criteria. The criteria are accessibility, aesthetics, and comfort. The research method is quantitative by collecting primary and secondary data. Data analysis involved comparing the criteria with conditions in the field based on the visitor questionnaire results. The research concludes that the PKP Park has applied city park criteria to accessibility, aesthetics, and comfort variables. Nevertheless, it is incomplete, thus reducing the comfort of visitors in PKP Park